1976
DOI: 10.3750/aip1976.06.1.01
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of anisakid nematode larvae in Baltic cod (Gadus morhua callarias L.) and the dynamics of their invasion

Abstract: Larvae of two nematode species: Anisakis simplex (Rud.) and Contracaecum aduncum (Rud.) were found to occur in Baltic cod ( Gadus morhua callarias L.). Their occurrence in various fish organs was analyzed: the investigations covered also the invasion incidence fish size relationship, the annual variability of infestation, and its occurrence in different re gions of the Southern Baltic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Increase of anisakids infection level with age or length of the host, as well as decrease of infection in higher length classes, have been reported for several host species (Abaunza et al, 1995;Adroher et al;1996;Cruz et al, 2005;Fernández et al, 2005;Grabda, 1976;Manfredi et al, 2000;Valero et al, 2000). In the present work, the significant correlations obtained between host length and Anisakis sp.…”
Section: Discussionmentioning
confidence: 67%
“…Increase of anisakids infection level with age or length of the host, as well as decrease of infection in higher length classes, have been reported for several host species (Abaunza et al, 1995;Adroher et al;1996;Cruz et al, 2005;Fernández et al, 2005;Grabda, 1976;Manfredi et al, 2000;Valero et al, 2000). In the present work, the significant correlations obtained between host length and Anisakis sp.…”
Section: Discussionmentioning
confidence: 67%
“…The Anisakis simplex larvae belong to this group of nematodes. The first identified Anisakis-caused case was noted in 1955 in Holland, and from then on, the anisakidosis was recorded both in Holland and other European countries; the population of Japan, habitually consuming raw fish, is particularly vulnerable to the disease (Grabda 1976). Kennedy (1997) suggested that if the use of parasites as indicators of pollution can be justified, the fish host species must be abundant and easily accessible, and the species of parasite, despite their overdispersed distribution, must show a high prevalence and abundance in the fish population.…”
Section: Introductionmentioning
confidence: 98%
“…Previous investigations on salmon caught in the Atlantic documented that a number of marine parasite species, such as Anisakis simplex, are prevalent (Beverley-Burton & Pippy 1978, Margolis & Arthur 1979, Murphy et al 2010, and it is noteworthy that this was absent in the Baltic salmon. This indicates that Baltic salmon do not leave the Baltic, because the A. simplex life cycle is restricted to more marine areas and not completed in the Baltic proper (Grabda 1974(Grabda , 1976. Migrating North Sea herring (springspawning Rügen herring) entering the Baltic from the North Sea during autumn in order to spawn along the German and Polish coastlines (Grabda 1974, 1976, Mehrdana et al 2014) are infected with A. simplex, and the nematode can be transferred to local predatory fish, such as cod, feeding on this herring stock.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Baltic salmon do not leave the Baltic, because the A. simplex life cycle is restricted to more marine areas and not completed in the Baltic proper (Grabda 1974(Grabda , 1976. Migrating North Sea herring (springspawning Rügen herring) entering the Baltic from the North Sea during autumn in order to spawn along the German and Polish coastlines (Grabda 1974, 1976, Mehrdana et al 2014) are infected with A. simplex, and the nematode can be transferred to local predatory fish, such as cod, feeding on this herring stock. However, the absence of this nematode in the present study indicates that Baltic salmon do not feed on long-range migrating North Sea herring in the western Baltic, and the absence of characteristic marine trematodes such as Lecithaster gibbosus and Derogenes varicus, which are known from salmon in the Atlantic (Dogiel & Petruschevski 1934), further reflects the local migration of Baltic salmon within the Baltic Sea.…”
Section: Discussionmentioning
confidence: 99%